Technological applications in sustainable urban logistics: a systematic review with bibliometric analysis - Oguz, Suzan; Tanyas, Mehmet (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Today, supply chains and logistics operations in urban areas face increasing customer demands for productivity, quality, sustainability and traceability. Traditional methods cannot adequately respond to the rapidly changing challenges and requirements of this sector. Therefore, new methods have been developed to make urban logistics activities more modern, environmentally sensitive and integrated with technology. This research aims to identify sustainable urban logistics and the role of technological applications on urban logistics. In this research, which is designed as a systematic study, firstly, based on the existing literature, the basic concepts, trends, researchers and countries working in the field of sustainable urban logistics are examined by bibliometric analysis method. It is observed that the most frequently used technology applications in sustainable urban logistics are last mile delivery, vehicle routing, optimisation, electric vehicles and crowdsourcing applications. This study is expected to contribute to the development and sustainability of urban logistics.